A randomized controlled trial of WATAAP to promote physical activity in colorectal and endometrial cancer survivors. Issue 7 (26th April 2019) - Maxwell‐Smith, Chloé; Hince, Dana; Cohen, Paul A.; Bulsara, Max K.; Boyle, Terry; Platell, Cameron; Tan, Patrick; Levitt, Michael; Salama, Paul; Tan, Jason; Salfinger, Stuart; Makin, Gregory; et al.
Abstract: Objective: The objective of this study was to ascertain whether wearable technology coupled with action planning was effective in increasing physical activity (PA) in colorectal and endometrial cancer survivors at cardiovascular risk. Methods: Sixty‐eight survivors who had cardiovascular risk factors and were insufficiently active were randomized to intervention and control arms. Intervention participants were given a wearable tracker for 12 weeks, two group sessions, and a support phone call. Participants in the control arm received print materials describing PA guidelines. Assessments at baseline and 12 weeks measured triaxial and uniaxial estimates of moderate‐vigorous physical activity (MVPA), sedentary behaviour, blood pressure, and body mass index (BMI). Results: The intervention group significantly increased MVPA by 45 min/wk compared with a reduction of 21 min/wk in the control group. Group by time interactions were significant for minutes of MVPA ( F 1, 126 = 5.14, P = 0.025). For those with diastolic hypertension, there was a significant group by time interaction ( F 1, 66 = 4.89, P = 0.031) with a net reduction of 9.89 mm Hg in the intervention group. Conclusions: Significant improvements in MVPA were observed following the intervention. The results display promise for the use of pragmatic, low‐intensity interventions using wearable technology.